EKONOMI POLITIK ISLAM: PEMIKIRAN, PERGERAKAN DAN PERKEMBANGAN NYA DI INDONESIA - Nasrullah, Aan (Ahkam: Jurnal Hukum Islam, 2018)
One of the dominant factors affecting the economic performance of a country is the political economy system used. The thougt and movement of Islamic political economic system will also affect the economic and financial practices of sharia (Islam). In the economic-political context, Indonesia is more likely to use a pattern of political systems that the government is to engage and interfere the economic and business fields. The movements of Islamic political economy in Indonesia based on periods are as the following: (1) at the beginning of independence and the period of the Old Order, the practice of Islamic political economy is reflected from the thoughts of the nation founding father, M. Hatta, with the concept of Indonesian Socialism or Religious Socialism. (2) in the New Order era, the political economy of Islam tends to disappear due to economic policy and political system at this time. (3) the politics of the reform period have a positive effect on the movement and development of Islamic economic politics. Stakeholders such as governments, academics and practitioners contribute actively to the movement of Islamic political economy.Keywords: Political Economy of Islam, Thought and Movement